Diseño de branding de la empresa florícola Rosas Premium para el desarrollo de estrategias de fidelización de clientes de la provincia de Cotopaxi. - Herrera Teneda, Carolina Mercedes (2023)
This project aims to generate branding strategies for customer loyalty in the province of Cotopaxi of the company Rosas Premium within a market as competitive as the flower sector. There is a great demand with respect to this type of floriculture, and for this the company seeks to establish strategies that generate loyalty in its customers, to achieve the objective passed through a series of stages guided by the previous study through: surveys, interviews, SWOT and a field study, all this to have a clearer vision of how theconditions in the sector are and the improvements that can be achieved for the company.Strategies were developed that have been carefully analyzed to be subsequently implemented, so it is feasible to highlight the product in each aspect, such as its new visual identity, which will help to get a better recognition within the market, all this being implemented also in different types of (social) media that have been analyzed within the established strategies.